2020
DOI: 10.1007/s00213-020-05603-y
|View full text |Cite
|
Sign up to set email alerts
|

Theory of mind in users of anabolic androgenic steroids

Abstract: Rationale Anabolic androgenic steroids are used to improve physical performance or increase lean muscle mass. About one-third of users develop a dependency syndrome, which is characterized by elevated rates of psychopathology, cognitive impairments, and aggressive and antisocial behaviors. The mechanisms behind these intra- and interpersonal problems are not known. Objective To examine theory of mind (ToM), i.e., the ability to infer the mental state of others, in users of anabolic androgenic steroids. Reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 57 publications
2
27
0
1
Order By: Relevance
“…The use of anger-related words is positively correlated with circulating testosterone levels and with polymorphisms in the androgen receptor gene (Mascaro et al, 2018), which make cells more susceptible to the masculinising influence of testosterone. These findings indicate the existence of a plausible biological mechanism (Geniole et al, 2019;Luoto et al, 2019a) which creates sex differences in anger-related language use as well as other psychobehavioural sex differences, including peoplethings orientation, risk-taking, and theory of mind (Khorashad et al, 2018;Luoto, 2020b;Vaskinn et al, 2020;Luoto and Varella, 2021). Furthermore, the finding of higher angerrelated words and sexual words in lesbian authors relative to heterosexual women is consistent with existing findings on psychobehavioural masculinisation in non-heterosexual women, including higher sociosexuality, sensation-seeking, psychopathy, and incarceration rates compared with heterosexual women (Luoto et al, 2019a,b) (though see Gil-Llario et al, 2015 who reported lower sexual sensation seeking in self-identified lesbians than in heterosexual women).…”
Section: Discussionmentioning
confidence: 82%
“…The use of anger-related words is positively correlated with circulating testosterone levels and with polymorphisms in the androgen receptor gene (Mascaro et al, 2018), which make cells more susceptible to the masculinising influence of testosterone. These findings indicate the existence of a plausible biological mechanism (Geniole et al, 2019;Luoto et al, 2019a) which creates sex differences in anger-related language use as well as other psychobehavioural sex differences, including peoplethings orientation, risk-taking, and theory of mind (Khorashad et al, 2018;Luoto, 2020b;Vaskinn et al, 2020;Luoto and Varella, 2021). Furthermore, the finding of higher angerrelated words and sexual words in lesbian authors relative to heterosexual women is consistent with existing findings on psychobehavioural masculinisation in non-heterosexual women, including higher sociosexuality, sensation-seeking, psychopathy, and incarceration rates compared with heterosexual women (Luoto et al, 2019a,b) (though see Gil-Llario et al, 2015 who reported lower sexual sensation seeking in self-identified lesbians than in heterosexual women).…”
Section: Discussionmentioning
confidence: 82%
“…En la revisión sistemática se incluyeron 7 estudios, de los cuales el 42.9% de las investigaciones fueron realizadas principalmente en Noruega (n = 3;Bjørnebekk et al, 2019;Hauger et al, 2020;Vaskinn et al, 2020), seguido por Inglaterra con el 42.9% (n = 3; Heffernan et al, 2015;Kanayama et al, 2013;Kaufman et al, 2015) y Estados Unidos con el 14.2% (n = 1; Hildebrandt et al, 2014). En cuanto a la población, la mayoría de los estudios estuvieron dirigidos a hombres (n = 6) y solo uno incluyó a mujeres.…”
Section: Resultsunclassified
“…The sample size of animal models ranged from 20 to 149, and the sample size of studies in humans ranged from 1 to 229. The majority of studies included all male samples, with one animal model [ 12 ] and one human study [ 13 ] stating that females were included in the sample.…”
Section: Resultsmentioning
confidence: 99%
“…Non-dependent androgen users demonstrated worse impulse inhibition and working memory relative to nonusers. Furthermore, in a related study, both male and female weightlifters who were dependent on androgens demonstrated impaired theory of mind, suggesting that prolonged androgen use may also impair social cognition [ 13 ]. However, it is important to note the cross-sectional nature of these studies, making it difficult to establish causality, and it is possible that reduced executive functioning and impaired theory of mind could be a premorbid risk factor for use and dependence.…”
Section: Brain Healthmentioning
confidence: 99%